Improving knowledge on safe medication management of inpatient children and adolescents: a pre-post study. Issue 7 (July 2022) - D'Amore, Carmen; Zama, Benedetta; Salotti, Rita; Raponi, Massimiliano; Atti, Marta Ciofi degli; Briganti, Vito; Buccione, Carla; Calvani, Mauro; Corsetti, Tiziana; Cortis, Elisabetta; Emma, Francesco; et al.
Abstract: Objective: The primary aim of this study was to assess the impact of an education intervention on knowledge regarding medication use in hospitalized children and adolescents. Methods: A pre-post multicentre study was conducted in pediatric wards of the hospitals in Lazio Region between July 2019-March 2021. An in-person education intervention was provided to hospitalized patients aged 6–15 years, able to understand spoken and written Italian language. Topics included: correct intake and management of medications at home. Prior and after the education intervention, we evaluated patient knowledge with a self-administered test. Results: One-hundred-and-four (n = 104) patients participated in the study. In the pre-education period, 79.8% of the patients answered correctly to at least 60% of the questions of the test; the lowest number of correct answers concerned medication intake (36.5%; 33.6%), food-drug interactions (44.2%), appropriate indication to use of antibiotics (36.5%) and antibiotic resistance (55.8%). After the education intervention, 100% of the patients completed the test correctly. Conclusion: The education intervention increased knowledge on several areas of interest, in children of different age-groups and including patients with chronic diseases. Practice Implications: Children's education is essential to encourage gradual transfer of responsibility for medication use, in ways that respect parental responsibilities and the health status and capabilities of the child. Highlights: Education for children and adolescents was useful in increasing knowledge on medication use. Items on medication intake and food-drug interactions showed the greatest improvement. One-to-one education was more effective in improving knowledge than group lessons.